Effectiveness of Technical-Vocational Training Programs on Livelihood Opportunities of Out-of-School Youth in Lingayen, Pangasinan, Philippines - Soriano, PhD, Randy F.; Caburnay, Jessa Mae V.; Abalos, Laurence R.; Lorenzo, Vanessa C. (Asian Journal of Multidisciplinary Studies, 2024)
This study was conducted to assess the effectiveness of vocational training programs in enhancing the livelihood opportunities of out-of-school youth in Lingayen, Pangasinan. Specifically, it examined the demographic profile of the respondents, the level of effectiveness of vocational training in terms of relevance to employment, confidence and readiness for employment, practical application and hands-on experience, and awareness of job opportunities. It also aimed to identify the challenges encountered in participating in such programs and determine the significant relationship between the respondents’ profile and the perceived effectiveness of vocational training. The research employed a descriptive-correlational design using a survey questionnaire distributed to 67 out-of-school youth through convenience sampling. Data were analyzed using frequency, percentage, weighted mean, and Pearson Chi-Square test. Findings revealed that vocational training programs are perceived to be highly effective across the four aspects. Further the challenges encountered were rated as slightly challenging. Moreover, researchers determined that there is no significant relationship between the demographic profiles of out-of-school and the perceived effectiveness of vocational training programs on their job opportunities. Based on the findings, it recommends that training programs should tailor to the specific characteristics of out-of-school youth in Lingayen, Pangasinan, Philippines.